ANALISIS PENINGKATAN CAPAIAN KINERJA ASN DI KANTOR KECAMATAN PRABUMULIH BARAT KOTA PRABUMULIH - Supriadi Supriadi; Ismandra Ismandra; Hendry Wijaya; Fitri Septia; Iin Indraswari; Rulli Ramadhayani; Rieka Saimona Rieka Saimona (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to explain whether the independent research variables (Work Environment, Work Motivation, Promotion) have an influence on improving ASN performance at the Prabumulih Barat District Office, Prabumulih City. Data were analyzed using Descriptive Qualitative Methods. Research Data Collection Techniques using direct interviews with several staff of the Prabumulih Barat District Office, Prabumulih City. valued and feel given a boost of motivation in carrying out their job obligations, as well as positions that involve them in planning promotions for them and are given according to the performance they can make will make them more diligent and improve their performance at work. Keywords: Work Environment, Work Motivation, Promotion, Employee Performance.